PERFORMANCE EVALUATION OF IMMGRATION POLYTECHNIC CADETS SOCIALIZATION AT THE IMMIGRATION OFFICE CLASS ONE OF BORDER CONTROL BANDAR LAMPUNG - Muhammad Alvi Ghazy; s Sohirin (Jurnal Abdimas Imigrasi, 2021)
As social beings, humans are given by God to be able to work with each other in order to produce a better community. There are many ways that can be done to meet these expectations, one of which is by conducting socialization activities that can be carried out by one community group against other community groups. For example, what was done by the Immigration Polytechnic cadets during this year's Latjapura activity, where the Immigration Polytechnic cadets and cadets were given special powers by the Immigration Polytechnic to carry out socialization activities where they carried out Latjapura activities. Bandar Lampung, as one of the destinations for the Immigration Polytechnic cadets to carry out Latjapura activities has an Immigration Office Class 1 TPI Bandar Lampung to make this happen, namely outreach activities involving the community, especially the people of the city of Bandar Lampung.